O10 Risk factors for ankle sprain injury in youth soccer and basketball. (17th September 2017) - Owoeye, OBA; Palacios-Derflingher, LM; Emery, CA
Abstract : Study Design: Secondary analysis of pooled data from 3 cohort and 2 randomised controlled studies. Objectives: To evaluate risk factors for ankle sprain injury (ASI) in youth soccer and basketball. Background: ASI is the most common injury in youth soccer and basketball. Risk factors for injury in professional soccer and basketball are generally well investigated. However, little is known about the risk factors specifically for ASI at all levels in these sports. Identifying risk factors specific for ASI in youth soccer and basketball will inform explicit recommendations for ankle sprain prevention strategies for players. Methods and Measures: We pooled data from a total of 2265 male and female youth soccer and basketball players (11–18 years) in Alberta, Canada (2005–2011) [mean age (SD)=15 (1.45) years; range=11–18 years] with 150, 818 hours of exposure. ASI was the primary outcome and was recorded using a validated prospective injury surveillance system consistent in all studies. Potential risk factors evaluated included sex, age, weight, height, BMI, sport, previous ASI, and previous lower extremity injury (LEI) (with or without previous ASI in the past 1 year). Univariate and multivariable Poisson regression, controlling for clustering by team and offset for exposure hours, was used to evaluate all covariates as potential risk factors with considerations for confounding (including exposure to neuromuscular training) and effect modification. Results: Independent risk factors for ASI included previous ASI [IRR=1.98 (95% CI; 1.38–2.81)] and participation in basketball vs. soccer [(IRR=1.83 (95% CI; 1.18–2.85)). Sex, age, BMI, and previous LEI (without previous ASI) did not predict ASI (p>0.05). Conclusions: Risk of ASI in youth basketball is greater than soccer and players with a history of ASI are at greater risk. Sex, age, BMI, and previous LEI (excluding previous ASI) do not predict ASI in youth soccer and basketball.